2024
DOI: 10.1097/qai.0000000000003370
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Long-Acting Injectable HIV Pre-Exposure Prophylaxis Implementation in Primary Care Since Its Approval in the United States

Shimrit Keddem,
Sneha Thatipelli,
Omaris Caceres
et al.

Abstract: Background: HIV pre-exposure prophylaxis (PrEP) is a highly effective method to mitigate the HIV epidemic, but uptake of PrEP has been slow and is associated with racial and gender disparities. Oral PrEP requires high levels of adherence to be effective, which may disadvantage certain high-risk groups. The first injectable HIV PrEP, a drug given every two months rather than as a daily pill, was approved by the FDA in December 2021. Setting: A Family Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Potential facilitators for PrEP accessibility offered by LA-PrEP documented in recent literature include periodic (instead of daily) administration which may reduce logistical barriers and social stigma [ 23 ]. However, since FDA approval of LA-PrEP, access has been hampered by challenges in the logistics of service provision and user insurance coverage, [ 24 26 ] as well as low awareness and low trust in LA-PrEP [ 27 ]. While estimates are not widely available, ViiV Healthcare reported that 11,000 people were taking LA-PrEP in the U.S. as of 2023 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potential facilitators for PrEP accessibility offered by LA-PrEP documented in recent literature include periodic (instead of daily) administration which may reduce logistical barriers and social stigma [ 23 ]. However, since FDA approval of LA-PrEP, access has been hampered by challenges in the logistics of service provision and user insurance coverage, [ 24 26 ] as well as low awareness and low trust in LA-PrEP [ 27 ]. While estimates are not widely available, ViiV Healthcare reported that 11,000 people were taking LA-PrEP in the U.S. as of 2023 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%